2002
DOI: 10.1046/j.1471-4159.2002.01236.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered processing of amyloid precursor protein in the human neuroblastoma SH‐SY5Y by chronic hypoxia

Abstract: Alzheimer's disease (AD) is more prevalent following an ischemic or hypoxic episode, such as stroke. Indeed, brain levels of amyloid precursor protein (APP) and the cytotoxic amyloid b peptide (Ab) fragment are enhanced in these patients and in animal models following experimental ischaemia. We have investigated the effect of chronic hypoxia (CH; 2.5% O 2 , 24 h) on processing of APP in the human neuroblastoma, SH-SY5Y. We demonstrate that constitutive and muscarinic-receptor-enhanced secretion of the a-secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 50 publications
0
40
1
Order By: Relevance
“…Another study, however, using AD transgenic mice overexpressing mutant APP showed that neither expression nor activity of BACE was significantly affected by ischemic insult; instead ADAM10 was markedly increased in the early stage of ischemic insult and then down-regulated at later stages (41). Other studies report a drastic decrease in ADAM10 and TACE protein levels with unchanged BACE1 levels in human neuroblastoma SH-SY5Y cells subjected to chronic hypoxic treatments (42)(43)(44). While it is hard to reconcile these results, differing experimental procedures, such as cells/tissues examined, culture conditions, the percentage of O 2 utilized, or duration of hypoxic treatment, could all contribute to discrepant results.…”
Section: Discussionmentioning
confidence: 99%
“…Another study, however, using AD transgenic mice overexpressing mutant APP showed that neither expression nor activity of BACE was significantly affected by ischemic insult; instead ADAM10 was markedly increased in the early stage of ischemic insult and then down-regulated at later stages (41). Other studies report a drastic decrease in ADAM10 and TACE protein levels with unchanged BACE1 levels in human neuroblastoma SH-SY5Y cells subjected to chronic hypoxic treatments (42)(43)(44). While it is hard to reconcile these results, differing experimental procedures, such as cells/tissues examined, culture conditions, the percentage of O 2 utilized, or duration of hypoxic treatment, could all contribute to discrepant results.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hypoxia leads to downregulation, in neurons, of the expression of ADAM10, a candidate protein for α-secretase which is essential to the processing of APP through the nonamyloidogenic pathway [85]. On the other hand, the level and activity of β-secretase (BACE-1), an enzyme that participates of the breakdown of APP through the amyloidogenic pathway, are both increased by the upregulation of hypoxia-inducible factor 1α (HIF-1-α) caused by hypoxia [86][87][88].…”
Section: Hypoxia Induced By Sleep Disordered Breathing (Sdb) Emamianmentioning
confidence: 99%
“…The cells were then transferred to 24-well plates filled with poly-L-lysine, rinsed with PBS and treated with Eu(NO 3 ) 3 . Cell viability was assessed using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT, Sigma, Thermo Fisher Scientific (Life Technologies) PaisleyPA4 9RF, UK) reduction assay as described previously [28][29][30]. Absorbance of the cells was measured using a spectrophotometer at a test wavelength of 570 nm and a reference wavelength of 630 nm.…”
Section: In Vitro Cell Culture and Cell Viability Testmentioning
confidence: 99%
“…A few studies focused on the toxicological effects of RE ions using human osteosarcoma cell line MG63, umbilical cord perivascular cell and mouse macrophages; reported large concentration or systemic accumulation of these ions could lead to acute pathology and cellular toxicity [29,30]. However, these studies produce variable results.…”
Section: Introductionmentioning
confidence: 99%